2006
DOI: 10.1007/s00213-006-0610-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nornicotine enantiomers on intravenous S(−)-nicotine self-administration and cardiovascular function in rats

Abstract: Both R(+)- and S(-)-nornicotine may have potential utility as a novel tobacco use cessation agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As stated previously, biphasic patterns on nicotine intake have been observed with bupropion depending on the dose administered, and there is much speculation regarding the mechanism behind these differential effects. However, it has been suggested that bupropion's effects on nicotine addiction lie outside the primary or conditioned reinforcing effects of nicotine (Liu et al , 2008, Paterson et al , 2007, Paterson et al , 2008, Stairs et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…As stated previously, biphasic patterns on nicotine intake have been observed with bupropion depending on the dose administered, and there is much speculation regarding the mechanism behind these differential effects. However, it has been suggested that bupropion's effects on nicotine addiction lie outside the primary or conditioned reinforcing effects of nicotine (Liu et al , 2008, Paterson et al , 2007, Paterson et al , 2008, Stairs et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Stable responding was defined as three consecutive sessions with less than 25% variation in the total number of responses during the cocaine components and at least a 2:1 ratio in the number of responses on the cocaine lever compared to the sucrose lever during the cocaine components. Using these criterion, which our laboratory have use previously with a simple FR schedule (Stairs et al, 2007), 12 animals acquired stable cocaine self-administration after 12–14 sessions; 3 other rats did not reach criteria and 3 had a catheter malfunction that prevented inclusion of the data. Once responding stabilized, varying doses of SCH 23390 (0, 2.5, 5, and 10 µg/kg, s.c.) were administered in a latin square design 25 min prior to the session.…”
Section: Methodsmentioning
confidence: 99%
“…Nornicotine has been shown to support self-administration by itself, but higher doses are required and lower response rates are attained (Bardo et al, 1999). Conversely, large doses of nornicotine administered to rats prior to a nicotine self-administration session also inhibited nicotine self-administration (Green et al, 2000;Stairs et al, 2007). Additional studies not utilizing self-administration also suggest that the minor alkaloids may have actions relevant to reward (Dwoskin et al, 1995;Green, Brown, Phillips, Dwoskin, & Bardo, 2002;Papke, Dwoskin, & Crooks, 2007).…”
Section: Could Other Constituents Of Tobacco Impact the Threshold Formentioning
confidence: 99%